Role of Distinct Mitogen-Activated Protein Kinase Pathways and Cooperation between Ets-2, ATF-2, and Jun Family Members in Human Urokinase-Type Plasminogen Activator Gene Induction by Interleukin-1 and Tetradecanoyl Phorbol Acetate - Cirillo, Grazia (American Society for Microbiology, 1999)
We have investigated the in vivo and in vitro regulation of the human urokinase-type plasminogen activator (uPA) gene by interleukin-1 (IL-1) and analyzed the transcription factors and signalling pathways involved in the response of the −2.0-kb uPA enhancer to IL-1 induction and to tetradecanoyl phorbol acetate (TPA) induction. Mutational analysis showed the cooperative activity of the Ets-binding site (EBS) and the two AP-1 elements of the enhancer. The results reveal that the EBS is required for the response to both inducers mediated by Ets-2, which is regulated at a level subsequent to DNA binding, by an IL-1- and phorbol ester-inducible transactivation domain. Both the IL-1 and the TPA-mediated induction result in a drastic increase of AP-1 binding to the downstream site of the enhancer (uPA 3′ TPA-responsive element), while a mostly qualitative change, resulting from the interplay between ATF-2 homodimers and c-Jun–ATF-2 heterodimers, takes place at the upstream AP-1 element. The analysis of two distinct mitogen-activated protein kinase pathways shows that stress-activated protein kinase–Jun N-terminal kinase activation, resulting in the phosphorylation of ATF-2, c-Jun, and JunD, is required not only for the IL-1- but also for the TPA-dependent induction, while the extracellular signal-related kinase 1 (ERK-1) and ERK-2 activation is involved in the TPA- but not in the IL-1-dependent stimulation of the uPA enhancer.